Parental perceived stress among mothers of neonates admitted in neonatal intensive care unit at a teaching hospital of Gandaki province - Singh, Nitu Kumari; Gurung, Rajmi (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Neonatal Intensive Care Unit admission may be traumatic for mothers, causing psychological distress and altered parenting roles. This study aimed to assess the perceived parental stress (PPS) level and experience of mothers of neonates admitted to the NICU at a tertiary hospital in Gandaki Province. Methods: A mixed-method approach was used. For the quantitative study, 68 mothers of neonates admitted to the NICU were selected through total enumeration. A face-to-face interview using a structured questionnaire was conducted. PSS was measured using the PSS: NICU tool. For the qualitative study, ten mothers were selected purposively, and in-depth interviews were conducted using an interview guideline. The study was conducted at Gandaki Medical College Teaching Hospital and Research Center from May to June, 2024. Results: Of the total 68 mothers, 52(76.5%) had a low level of PPS. The highest mean stress score was in the “Baby’s Appearance and Behavior” subscale (31.97±16.96) out of a maximum 95 score, followed by “Relationship with Baby and Parental Role” (23.14±8.79) out of a maximum 50. Qualitative findings revealed deeper emotional struggles, including anxiety, helplessness, sleep disturbances, and fear of medical procedures. Conclusions: Despite low reported PPS levels, qualitative insights revealed emotional struggles and psychological burdens among mothers. Comprehensive support systems and emotionally responsive care are essential in NICUs to address these hidden stressors and enhance maternal coping.